Decatungstate-photocatalysed C(sp3)–H azidation. Issue 31 (29th March 2022) - Lu, Yen-Chu; Kao, Shih-Chieh; West, Julian G.
Abstract : Tetrabutylammonium decatungstate (TBADT) functions as an efficient photocatalyst for the C(sp 3 ) azidation of organic molecules using the commercial azide source para -acetamidobenzenesulfonyl azide ( p -ABSA). Abstract : C–H Azidation is an increasingly important tool for bioconjugation, materials chemistry, and the synthesis of nitrogen-containing natural products. While several approaches have been developed, these often require exotic and energetic reagents, expensive photocatalysts, or both. Here we report a simple and general C–H azidation reaction using earth-abundant tetra- n -butylammonium decatungstate as a photocatalyst and commercial p -acetamidobenzenesulfonyl azide ( p -ABSA) as the azide source. This system can azidate a variety of unactivated C(sp 3 )–H bonds in moderate to good yields and excellent turnover numbers. Preliminary mechanistic experiments implicate a radical mechanism proceeding via photo-hydrogen atom transfer (photo-HAT).